Improving The Methodology of Using Open Information Educational Facilities for Biology Teachers in The System of Professional Development - Khushnud Safarbayevich Nurmetov; Oygul Odil kizi Rasulova (Euro Asian Journal Publishing, 2024)
In this article a special attention is paid to the development of professional competencies of pedagogues on the basis of continuity, consistency and increasing natural science literacy in the field of teacher education and training, educating young people at the global level, in particular, expanding the pedagogical capabilities of teaching exact and natural sciences, enriching the practical and applied content of the education system, student learning as well. Research and analysis conducted within the framework of a project such as PISA, TIMSS to assess social literacy and student literacy, aimed at teaching natural sciences in educational institutions, introducing new approaches to traditional education, improving the pedagogical process, enriching the content of education based on didactic principles , increasing the level of organization and management of the educational process present information on the continuous monitoring and control of processes for improving indicators of levels of efficiency in the use of information and communication technologies while increasing the effectiveness of training and qualification of biology teachers.
Keywords: Multimedia; GIF animation; integration